Transcriptomic Responses of Mycoplasma bovis Upon Treatments of trans-Cinnamaldehyde, Carvacrol, and Eugenol - Ranjitkar, Saurav; Duan, Jingyue Ellie; Srirattana, Kanokwan; Alqahtani, Fahad; Tulman, Edan R.; Mandoiu, Ion; Venkitanarayanan, Kumar; Tian, Xiuchun (Frontiers in Microbiology, 2022)
Mycoplasma bovis (M. bovis) is an insidious, wall-less primary bacterial pathogen that causes bovine pneumonia, mid-ear infection, mastitis, and arthritis. The economic losses caused by M. bovis due to culling, diminished milk production, and feed conversion are underestimated because of poor diagnosis/recognition. Treatment with common antibiotics targeting the cell wall is ineffective. Plant-derived antimicrobials (PDAs) such as food-grade trans-cinnamaldehyde (TC), eugenol (EU), and carvacrol (CAR) are inexpensive and generally regarded as safe to humans and animals yet possess strong anti-bacterial properties. In preliminary studies, we found that all three PDAs inhibited the growth of M. bovis in vitro. Through RNA sequencing, we report here that CAR affected the expression of 153 genes which included the down-regulation of energy generation-related proteins, pentose phosphate pathway, and up-regulation of ribosomes and translation-related proteins. Few differentially expressed genes were found when M. bovis were treated with TC, EU, or when the three PDAs were double or triple combined. Our results suggest that, as opposed to the effect of CAR, the growth inhibitory effects of TC and EU at levels tested may be exerted through mechanisms other than gene expression regulations.